Production and partial characterization of lipase from Penicillium verrucosum obtained by submerged fermentation of conventional and industrial media - Pinheiro,Thaís da Luz Fontoura (2008)
The growing interest in lipase production is related to the potential biotechnological applications that these enzymes present. Current studies on lipase production by submerged fermentation involve the use of agro-industrial residues aiming at increasing economic attractiveness. Based on these aspects, the objective of this work was to investigate lipase production by Penicillium verrucosum in submerged fermentation using a conventional medium based on peptone, yeast extract, NaCl and olive oil, and an industrial medium based on corn steep liquor, Prodex Lac (yeast hydrolysate), NaCl and olive oil, as well as to characterize the crude enzymatic extracts obtained. Kinetics of lipase production was evaluated and the highest enzymatic activities, of 3.15 and 2.22 U.mL-1, were observed when conventional and industrial media were used, respectively. The enzymatic extract showed optimal activity in the range from 30 to 40 °C and at pH 7.0. Although the industrial medium presents economical advantages over the conventional medium, the presence of agro-industrial residues rich in nitrogen and other important nutrients seemed to contribute to a reduction in lipase activity.